The Struggles and Resilience of Women as Primary Earners in The Breadwinner (2017) Directed by Nora Twomey - Fatarani, Dyah Sukma (CV. Era Digital Nusantara, 2024)
The objective of this study is to identify women as the primary breadwinners depicted in the 2017 film The Breadwinner, directed by Nora Twomey. This research analyses the role of women as the main breadwinner in The Breadwinner (2017), the challenges faced by women in this role, and the representation of gender equality issues in the film. This researcher employs a feminist theoretical framework to analyse the data. This research employs a descriptive qualitative methodology. The data for this study are drawn from the film The Breadwinner (2017), comprising sentences, dialogues and scenes that are pertinent to the research topic. The findings indicate that women in this context assume the role of both family leaders and livelihood seekers. They face significant challenges, including the necessity to conceal their gender in order to secure their primary source of income, resisting social norms, and demonstrating courage in the face of risks. The film also reflects issues pertaining to gender equality, such as restricted access to education, employment discrimination, and limited mobility. The study emphasizes the importance of female empowerment. Parvana's determination to provide for her family and her defiance against social norms serve as an inspiration. It showcases the positive impact that empowered women can have on their families and communities.